High‐Temperature Annealing and Patterned AlN/Sapphire Interfaces. Issue 10 (27th July 2021) - Hagedorn, Sylvia; Mogilatenko, Anna; Walde, Sebastian; Pacak, Daniel; Weinrich, Jonas; Hartmann, Carsten; Weyers, Markus
Abstract : Using the example of epitaxial lateral overgrowth of AlN on trench‐patterned AlN/sapphire templates, the impact of introducing a high‐temperature annealing step into the process chain is investigated. Covering the open surfaces of sapphire trench sidewalls with a thin layer of AlN is found to be necessary to preserve the trench shape during annealing. Both the influence of annealing temperature and annealing duration are investigated. To avoid the deformation of the AlN/sapphire interface during annealing, the annealing duration or annealing temperature must be low enough. Annealing for 1 h at 1730 °C is found to allow for the lowest threading dislocation density of 3.5 × 10 8 cm −2 in the subsequently grown AlN, while maintaining an uncracked smooth surface over the entire 2 in. wafer. Transmission electron microscopy study confirms the defect reduction by high‐temperature annealing and reveals an additional strain relaxation mechanism by accumulation of horizontal dislocation lines at the interface between annealed and nonannealed AlN. By applying a second annealing step, the dislocation density can be further reduced to 2.5 × 10 8 cm −2 . Abstract : For AlGaN‐based UV light‐emitting diodes, it is advantageous to have a patterned interface between the AlN base layer and the sapphire substrate to improve the light extraction. Therefore, the combination of high‐temperature annealing and epitaxial lateral overgrowth is investigated to simultaneously reach a low threading dislocation density, a patterned AlN/sapphire interface, and a smooth AlN surface.